Amplicon sequencing detects mutations associated with pyrethroid resistance in Bemisia tabaci (Hemiptera: Aleyrodidae). Issue 6 (9th March 2021) - Wei, Yiyun; Guan, Fang; Wang, Ran; Qu, Cheng; Luo, Chen
Abstract: BACKGROUND: Bemisia tabaci (Gennadius) is a major damaging agricultural pest that exhibits high resistance to pyrethroid insecticides. L925I (TTA to ATA) and T929V (ACT to GTT) mutations in the para ‐type voltage‐gated sodium channel (VGSC) are associated with resistance of B. tabaci to pyrethroids. Amplicon sequencing is a reliable and highly efficient method to detect the frequency of mutations linked with insecticide resistance. RESULTS: Similar frequencies of L925I and T929V mutations were obtained by amplicon sequencing and Sanger sequencing (L925I: 0.3548 vs 0.3619; T929V: 0.6140 vs 0.6381) with overlap of 95% confidence interval in the SX population of B. tabaci . In five populations of B. tabaci from China, the maximum and minimum frequencies of the two mutations were found in the LN (L925I: 0.1126; T929V: 0.8834) and JS (L925I: 0.8776; T929V: 0.1166) populations by amplicon sequencing. However, there was no significant difference in frequencies between the L925I and T929V mutations. The sum frequency of L925I and T929V exceeded 0.9688 in all populations. In addition, a combining mutation, L925 + T929V (L925I and T929V located in same allele), was found in five populations by amplicon sequencing even though its highest frequency was only 0.0157. CONCLUSION: We established an efficient approach for detecting frequency of mutation by amplicon sequencing. The frequencies of L925I and T929V in VGSC associated with pyrethroid resistance were detected in this study, which could provide foundational data for resistance management of B. tabaci . © 2021 Society of Chemical Industry. Abstract : The frequencies of L925I and T929V mutations of the voltage‐gated sodium channel of Bemisia tabaci in five populations were detected by amplicon sequencing, whose reliability was verified by individual Sanger sequencing.